Teaching Learning Method Development With the Assignment to Outline Portions of the Textbook - Sarjito Surya (Bandar Lampung University (UBL), 2014)
Some of the problems are student’s interest and motivation are decrease and it effected on the passing grade students, the understanding of the students about the subject has decreased. The purpose on this paper is how to develop teaching learning method with assignment to outline portions of the textbook improve interest and motivation for effecting the passing rates in the class.